Water supplies from a sanitary point of view - Peck, Archie Carpenter (My University, 1896)
Introduction: Public water supplies for the smaller towns are gradually growing in favor. They are welcoming a common necessity and at the hand of the skillful engineers water is being placed at the doorway of all classes of people. Quality is attracting greater public attention and cast is being reduced to a minimum. Water has long been known to be the bearer of disease and the present attention that is being given to it places more emphasis upon the need of a more pure and wholesome article.
Citation: Peck, Archie Carpenter. Water supplies from a sanitary point of view. Senior thesis, Kansas State Agricultural College, 1896.
Morse Department of Special Collections
Keywords: Public water supplies; Quality; Engineering; Theses; Manuscripts (documents)